Cost analysis and control in banks - Cole, Leonard P. (Boston Bankers Publishing Company, 1985)
This book was designed as a practical and informative daily reference guide for cost analysis and control in banks. It should also be useful to a bank's chief financial officer, controller, asset / liability managers, management information systems analysts, as well as to bank personnel engaged in marketing, strategic planning, pricing, financial planning or budgeting, and profit improvement, to students enrolled in bank cost accounting or work measurement courses, and to consultants.
osc 14/05/2018
Loans
Keywords: Cost analysis and control; Bank management; Banks and banking